2020
DOI: 10.3390/ijms21207742
|View full text |Cite
|
Sign up to set email alerts
|

MYC in Brain Development and Cancer

Abstract: The MYC family of transcriptional regulators play significant roles in animal development, including the renewal and maintenance of stem cells. Not surprisingly, given MYC’s capacity to promote programs of proliferative cell growth, MYC is frequently upregulated in cancer. Although members of the MYC family are upregulated in nervous system tumours, the mechanisms of how elevated MYC promotes stem cell-driven brain cancers is unknown. If we are to determine how increased MYC might contribute to brain cancer pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 99 publications
(120 reference statements)
0
20
0
Order By: Relevance
“…[ 38 ] It has been reported that inhibition of this protein could result in the suppression of tumor growth. [ 39 ] Given that SadM‐CBE had a higher efficiency in the PAM‐proximal regions ( Figure 8 A ), it was a promising tool to introduce a stop codon in MYC via base editing for oncogene disruption. To further verify the superiority of SadM‐CBE for the editing of PAM‐proximal cytosines, the hyBE4max including a DNA binding protein RAD51 between APOBEC1 and Cas9 that was reported to have a broader editing window [ 40 ] was chosen for the comparison for the PAM‐proximal editing at six genomic loci.…”
Section: Resultsmentioning
confidence: 99%
“…[ 38 ] It has been reported that inhibition of this protein could result in the suppression of tumor growth. [ 39 ] Given that SadM‐CBE had a higher efficiency in the PAM‐proximal regions ( Figure 8 A ), it was a promising tool to introduce a stop codon in MYC via base editing for oncogene disruption. To further verify the superiority of SadM‐CBE for the editing of PAM‐proximal cytosines, the hyBE4max including a DNA binding protein RAD51 between APOBEC1 and Cas9 that was reported to have a broader editing window [ 40 ] was chosen for the comparison for the PAM‐proximal editing at six genomic loci.…”
Section: Resultsmentioning
confidence: 99%
“…MYC is a regulator of gene transcription and controls a diverse set of biological programs (28,29). MYC can promote programs of proliferative cell growth; thus, MYC is frequently up-regulated in tumors (30). MYC is associated with many cancers' progression (31).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, activation of p21 and p27 can occur using p53 and p73, for which L1 inhibition is also shown [321]. MYC proto-oncogene is involved in many cell processes and in the regulation of the cell cycle, the defects of which are often found in cancer [384]. MYC binding to the L1 5 UTR represses transcriptional activity.…”
Section: Regulation Of L1 By Cell Cycle Factorsmentioning
confidence: 99%